2015
DOI: 10.1007/s13566-015-0230-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of target delineation variability for thymic cancers: agreement evaluation of a prospective segmentation challenge

Abstract: Objectives We sought to quantitatively determine the inter-observer variability of expert radiotherapy target-volume delineation for thymic cancers, as part of a larger effort to develop an expert-consensus contouring atlas. Methods A pilot dataset was created consisting of a standardized case presentation with pre- and post-operative DICOM CT image sets from a single patient with Masaoka-Koga Stage III thymoma. Expert thoracic radiation oncologists delineated tumor targets on the pre- and post-operative sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Our work follows previous SWOG efforts made to address inter-observer variability across different organs sites [9] . In previous work, we showed that educational intervention with a SWOG-approved consensus atlas reduced inter-observer variability in rectal cancer target volume delineation [7] .…”
Section: Discussionmentioning
confidence: 98%
“…Our work follows previous SWOG efforts made to address inter-observer variability across different organs sites [9] . In previous work, we showed that educational intervention with a SWOG-approved consensus atlas reduced inter-observer variability in rectal cancer target volume delineation [7] .…”
Section: Discussionmentioning
confidence: 98%
“…29 In thymomas, only inter-observer variability between RTOs has been analyzed. 11 Currently, a lack of a standardized protocol for PORT in thymomas leads to only brief advice in international guidelines. 5,8 These results support our findings that a protocol and further research in optimal delineation of CTVs for thymomas in the post-resection setting is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,10 Accurate delineation of tumor volumes is a time-consuming and crucial step in radiotherapy, but it is also the most susceptible to human error. 11 Radiation oncologists (RTOs) are often dependent on descriptive language used by other specialists, such as surgeons and radiologists. 12 Computed tomography (CT)-based planning is used to determine the clinical target volume (CTV).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial inter-observer variations in target delineation have been presented in a number of previous studies [1][2][3][4][5][6][7][8][9]. The variations can be due to differences in interpretation of the diagnostic material, ambiguities in treatment protocols, lack of guidelines and/or inadequate, differences in local policies, the availability and use of multi-modality imaging, the subjective assessment of disease dissemination and/or the individual training and experience of the radiation oncologists.…”
Section: Introductionmentioning
confidence: 99%